2020
DOI: 10.3329/sja.v18i1.48390
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Different Cultivars of Mungbean in Coastal Region of Bangladesh

Abstract: The study was conducted at farmers’ field of Itbaria, Patuakhali sadarupazila under Patuakhali district during January to April 2016under the agro ecological zone AEZ-13 (Ganges Tidal Flood plain). This site was located in between 22°14' and 22°29' North latitudes and in between 90°12' and 90°28' East longitudes of Bangladesh. Fifteenmungbean varieties viz., BARI Mung-1, BARI Mung-2, BARI Mung-3, BARI Mung-4, BARI Mung-5, BARI Mung-6, BINA Moog-4, BINA Moog-5, BINA Moog- 6, BINA Moog-7, BINA Moog-8, BU Mug-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 2 publications
3
4
0
Order By: Relevance
“…It was mentioned here that the CSA technology also used 50% fewer fertilizers and also manures were added at the rate of 10 ton/ha rate. These two varieties have already proved to be the best production ability in Bangladesh (Islam et al, 2020), and the present study also found that mungbean production had quite better (1065 and 1047 kg/ha) in the disaster pruned Northeastern border region of Bangladesh. The results of the present study also supported the study of Islam et al (2020) in the mungbean production of Bangladesh.…”
Section: Results and Discussion Productionsupporting
confidence: 75%
See 4 more Smart Citations
“…It was mentioned here that the CSA technology also used 50% fewer fertilizers and also manures were added at the rate of 10 ton/ha rate. These two varieties have already proved to be the best production ability in Bangladesh (Islam et al, 2020), and the present study also found that mungbean production had quite better (1065 and 1047 kg/ha) in the disaster pruned Northeastern border region of Bangladesh. The results of the present study also supported the study of Islam et al (2020) in the mungbean production of Bangladesh.…”
Section: Results and Discussion Productionsupporting
confidence: 75%
“…The study used the high-yielding and short-duration tested mungbean varieties in the study area. The two varieties in Bangladesh namely, BARI Mung-6 and BINA Mung-8 have tested the best verity among the 16 different varieties in Bangladesh (Islam et al, 2020). Bangladesh Agriculture Research Institute (BARI-6) variety is medium plant structure, photo insensitive and resistant to major diseases.…”
Section: Mungbean Varietymentioning
confidence: 99%
See 3 more Smart Citations